2022
DOI: 10.1080/21655979.2022.2057632
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone protects cardiac microvascular endothelial cells against ischemia/reperfusion injury by binding to Sigma-1 Receptor

Abstract: Endothelial dysfunction is an important mechanism involved in myocardial ischemia-reperfusion (I/R) injury. We aimed to explore the effects of Oxycodone on myocardial I/R injury in vivo and in vitro to reveal its mechanisms related to Sigma-1 Receptor (SIGMAR1). A rat model of I/R-induced myocardial injury was developed. The ischemic area and myocardial histopathological changes after oxycodone addition were evaluated by TTC staining and H&E staining. LDH, CK-MB and cTnI levels were used to assess myocardial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Either pre or posttreatment with opioid have a clear myocardial protective effect (22). Oxycodone, as a potent opioid, was also proved to significantly improve myocardial ischemia-reperfusion, especially exerts a good inhibitory effect on apoptosis caused by ischemia-reperfusion injury(20) (23). Few reports are available for the effect of oxycodone in septic myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Either pre or posttreatment with opioid have a clear myocardial protective effect (22). Oxycodone, as a potent opioid, was also proved to significantly improve myocardial ischemia-reperfusion, especially exerts a good inhibitory effect on apoptosis caused by ischemia-reperfusion injury(20) (23). Few reports are available for the effect of oxycodone in septic myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is considered as the earliest stage in the development of cardiovascular disease, prior to the clinical manifestation of symptoms [ 22 ]. Apparently, endothelial dysfunction occurs in the microcirculation before affecting macrovascular structures [ 23 , 24 ], but most research in CKD-related CVD has been devoted to macrovascular complications [ 25 ]. CMECs, which account for one-third of the total number of heart cells, is the major cell type in the processes of cardiovascular angiogenesis and play a critical role in maintaining sufficient cardiac perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also demonstrated Sigmar1’s involvement in mitochondrial bioenergetics regulation in vascular and lymphatic endothelial cells. A recent study showed that the opioid receptor agonist, oxycodone, preserves cardiac microvascular endothelial cell integrity and myocardial function after ischemia-reperfusion injury by binding to Sigmar1 ( Ji et al, 2022 ). Pharmacologic inhibition of Sigmar1 using its antagonist, such as haloperidol metabolite-II valproate ester [(±)-MRJF22] exhibited an antiangiogenic effect, significantly reducing cell viability, migration, and tube formation in human retinal endothelial cells stimulated with vascular endothelial growth factor A ( Olivieri et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%